Genotoxic effects of mycotoxins - Ülger, Taha Gökmen; Uçar, Aslı; Çakıroğlu, Funda Pınar; Yilmaz, Serkan (Toxicon (Oxford), 2020)
Fungi produce mycotoxins in the presence of appropriate temperature, humidity, sufficient nutrients and if the density of the mushroom mass is favorable. Although all mycotoxins are of fungal origin, all toxic compounds produced by fungi are not called mycotoxins. The interest in mycotoxins first started in the 1960s, and today the interest in mycotoxin-induced diseases has increased. To date, 400 mycotoxins have been identified and the most important species producing mycotoxins belongs to Aspergillus, Penicillium, Alternaria and Fusarium genera. Mycotoxins are classified as hepatotoxins, nephrotoxins, neurotoxins, immunotoxins etc. In this review genotoxic and also other health effects of some major mycotoxin groups like Aflatoxins, Ochratoxins, Patulin, Fumonisins, Zearalenone, Trichothecenes and Ergot alkaloids were deeply analyzed.